ZBTB48 is both a vertebrate telomere-binding protein and a transcriptional activator - Jahn, A.; Rane, G.; Paszkowski-Rogacz, M.; Sayols, S.; Bluhm, A.; Han, C.; Draškovic, I.; Londoño-Vallejo, J.; Kumar, Alan Prem; Buchholz, F.; Butter, F.; Kappei, D. (2017)
Â© 2017 The Authors. Published under the terms of the CC BY 4.0 license Telomeres constitute the ends of linear chromosomes and together with the shelterin complex form a structure essential for genome maintenance and stability. In addition to the constitutive binding of the shelterin complex, other direct, yet more transient interactions are mediated by the CST complex and HOT1/HMBOX1, while subtelomeric variant repeats are recognized by NR2C/F transcription factors. Recently, the Kruppel-like zinc finger protein ZBTB48/HKR3/TZAP has been described as a novel telomere-associated factor in the vertebrate lineage. Here, we show that ZBTB48 binds directly both to telomeric and to subtelomeric variant repeat sequences. ZBTB48 is found at telomeres of human cancer cells regardless of the mode of telomere maintenance and it acts as a negative regulator of telomere length. In addition to its telomeric function, we demonstrate through a combination of RNAseq, ChIPseq and expression proteomics experiments that ZBTB48 acts as a transcriptional activator on a small set of target genes, including mitochondrial fission process 1 (MTFP1). This discovery places ZBTB48 at the interface of telomere length regulation, transcriptional control and mitochondrial metabolism.